Cyclin G1 Regulates the Alveolarization in Models of Bronchopulmonary Dysplasia by Inhibiting AT2 Cell Proliferation - Panpan Xu; Wanqing Zhuo; Peipei Zhang; Ying Chen; Yue Du; Ying Li; Yajuan Wang (Biomolecules)
Disrupted neonatal lung alveologenesis often leads to bronchopulmonary dysplasia (BPD), the most common chronic lung disease in children. The inhibition of type 2 alveolar (AT2) cell proliferation plays an important role in the arrest of alveologenesis. However, the mechanism of AT2 cell proliferation retardation in BPD is still not fully elucidated. The purpose of the present study was to explore the effects of cyclin G1 (CCNG1) on AT2 cell proliferation in hyperoxia-induced lung injury in neonatal mice. Our findings revealed that hyperoxia significantly reduced the proportion of AT2 cells in the lungs of neonatal mice and coincided with an upregulation of CCNG1 expression. Notably, this upregulation of CCNG1 was accompanied by an increase in Wnt signaling. We observed colocalization of CCNG1 and Wnt3a within AT2 cells in the hyperoxia group. Further analysis showed that inhibiting CCNG1 expression regressed the expression of Wnt signaling and enhanced cell proliferation. These results suggest that CCNG1 plays a pivotal role in suppressing AT2 cell proliferation, at least partly by counteracting the effects of Wnt signaling to modulate AT2 cell growth in the BPD model. Our findings contribute to a better understanding of the mechanisms underlying BPD.